(untitled) (Singaporean Journal of Business Economics and Management, 2014)
The study focuses on the impact of training and development on employee performance at ESCON. Training and development is a critical process, which seeks to improve the performance of workers in the organisation. In order to form competent committees, employees’ relevant expertise and intellectual capacity needs to be improved. Some of the projects executed by ESCON fail at an embryonic stage owing to the fact that tenders are awarded to the lowest priced contractor. Moreover, the ineffectiveness of training and development of employees in the organisation reduces the organisation’s productivity, as organisations depend on having people with the right skills, attitudes and capabilities in order to reach goals effectively.